Blastocystosis: Epidemiological, clinical, pathogenic, diagnostic, and therapeutic aspects // Blastocistosis: Aspectos epidemiológicos, clínicos, patogénicos, diagnósticos y terapéuticos - Vielma, José Ramón (Investigación Clínica, 2020)
AbstractBlastocystisis a nonmoving pleomorphic stramenopile or chromist. Nineteen subtypes of this organism have been identified. It has a worldwide distribution. The prevalence rates in humans are lower than 1% in developed countries and up to 100% in developing countries. It is possible to recognize the fecal-oral transmission, through ingestion of contaminated food and water, and zoonotic spreads. The diagnosis is carried out by direct fecal examination, culture and molecular techniques. Blastocystis has virulence factors such as cysteine proteases, serine proteases and legumains, mostly secreted to the pathogen-host interface. This stramenopile has been linked to gastrointestinal symptoms, irritable bowel syndrome, urticarial and arthritis. However, there is not any conclusive evidence of association with the disease. Recently, the hypothesis of the opportunistic pathogen has emerged. Treatment has traditionally been based on metronidazole and other imidazoles. The recent obtaining of the nuclear genome will allow the rational development of new effective drugs. The aim of this review is to highlight the main epidemiological, clinical, pathogenic, diagnostic and therapeutic aspects of the Blastocystisinfection.ResumenBlastocystises un stramenopile o cromista, pleomórfico, no móvil. Se han identificado diecinueve subtipos (genotipos) de este organismo. Tiene una distribución mundial. Las tasas de prevalencia en humanos son inferiores al 1% en los países desarrollados, y hasta el 100% en los países en desarrollo. Se reconoce la transmisión fecal-oral, a través de la ingestión de alimentos y aguas contaminadas y la transmisión zoonótica. El diagnóstico se lleva a cabo mediante examen fecal directo, cultivo ytécnicas moleculares. Blastocystistiene factores de virulencia tales como proteasas de cisteína, proteasas de serina y legumaínas, principalmente secretadas a la interface patógeno-hospedador. Este stramenopile se ha relacionado con síntomas gastrointestinales, síndrome de intestino irritable, urticaria y artritis. Sin embargo, no hay pruebas concluyentes de asociación con la enfermedad. Recientemente, ha surgido la hipótesis de patógeno oportunista. El tratamiento tradicionalmente se ha basado en metronidazol y otros imidazoles relacionados. La reciente obtención del genoma nuclear permitirá el desarrollo racional de nuevas drogas efectivas. El objetivo de esta revisión es destacar los principales aspectos epidemiológicos, clínicos, patogénicos, diagnósticos y terapéuticos de la infección por Blastocystis.